Italian Women Writers : Gender and Everyday Life in Fiction and Journalism, 1870-1910 - Mitchell, Katherine (Book collections on Project MUSE., 2014)
Italian Women Writers looks at the work of three of the most significant women in late nineteenth century Italy€whose domestic fiction and journalism addressed a growing female readership.